ERGONOMIC ANALYSIS IN SECTORS OF AN AEROBIC ACADEMY: INTERFERENCE AND LIMITATIONS (Fiep Bulletin - online, 2017)
In recent decades, the concern with the human body, linking the benefits of sports to human well-being has been growing worldwide. The gyms and physical condition has brought possible interventions to the pursuit of these aesthetic and salutary ideals. However, analysis of the life quality of teachers and components of these spaces has proven scarce in the literature, it is necessary to intervene with techniques and practices that benefit jobs, thinking on ergonomics and health of its employees. This research has as main purpose the ergonomic analysis and suggestion of possible interference in the two sectors processes of an aerobic gym, focusing on the aspects and ergonomic impacts of the studied stations. Given the above, it was possible to identify necessary changes and that can interfere with the performance of employees in the short and long term.
Keywords: Ergonomic Analysis; Quality of Life; Ergonomics in Aerobic Academies